TICKET SCALPING – AI GONE TOO FAR? IN SEARCH OF AN OPTIMAL LEGAL SOLUTION - Stoyanov, Dimitar (International Journal of Legal and Social Order, 2025)
The rise of artificial intelligence (AI) has significantly transformed the ticketing industry, with the proliferation of ticket scalping bots posing a major challenge to fair consumer access. This paper explores the historical context of ticket scalping, its evolution in the digital age, and the legal and technological measures implemented to counteract its adverse effects. The discussion highlights key legislative responses, including the BOTS Act in the United States, the Digital Economy Act in the United Kingdom, and the EU’s Omnibus Directive, assessing their effectiveness in regulating AI-driven scalping practices. Additionally, the paper examines industry-led solutions such as blockchain-based ticketing and personalized tickets, alongside contractual restrictions imposed by event organizers. Through a comparative legal analysis, this study argues for a balanced approach that integrates legislative, technological, and contractual measures to mitigate AI-driven ticket scalping while ensuring fair access for consumers.